Cell Death and Proliferation Variability Caused by Different Dust Clay Minerals Using the Single‐Cell Method - Z. Ramirez‐Diaz; A. Deonarine; M. Plantier; N. Shaghaghi; K. Ardon‐Dryer (GeoHealth)
Abstract Dust storms are recurring atmospheric phenomena in arid and semiarid regions that decrease air quality and pose significant health risks. However, there is still no consensus on why some dust storms are more toxic than others. To understand the influence of dust on particle size and composition, in vitro experiments were performed evaluating the impact of five different clay minerals: montmorillonites (montmorillonite, Na‐rich montmorillonite, and Ca‐rich montmorillonite), illite, and kaolinite on human epithelial alveolar cells (A549) utilizing the Single‐Cell Analysis. Unlike other population techniques, this analysis monitors each cell individually by coupling fluorescent microscopy with an incubation system to continuously image the cells every 15 min for 48‐hr. This live‐cell imaging analysis was used to calculate the exact time of death, division rate, and type of death (apoptosis and necrosis). Ca‐rich Montmorillonite and Kaolinite were the most and least toxic clays, respectively. Although Ca‐rich Montmorillonite caused a significant increase in cell death and a decrease in cell proliferation compared to Kaolinite, both clays had a similar impact on the type of death (necrosis replaced apoptosis as the primary mechanism for cell death). Observations on the exact time of death show a significant increase in the rate of death between 34‐ and 48‐hr post‐exposure indicating a possible delay in health impact.